The influence of thermal fluctuations on Coulomb blockade edge in small Josephson junctions with linear growing of voltage - Askerzade, I.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
In this study we carried out the analysis of the thermal fluctuations on Coulomb blockade edge in small Josephson junctions with linear growing of voltage. It was shown that, charge fluctuation is determined by the energy ratio-parameter of small size Josephson junction, temperature and growing rate of voltage.